Was Zosimus of Panopolis Christian? - Dufault, Olivier (ARYS. Antigüedad: Religiones y Sociedades, 2022)
Zosimus of Panopolis, the first identifiable author of Greek alchemy, wrote in late-3rd or 4th-century CE Egypt. For over a century, scholars have pictured him in turn as Christian or as pagan. A reconsideration of Zosimus’ On the Letter Omega and the treatise known as the Final Count or Final Abstinence (teleutaia apochē) and the First Lesson on Excellence demonstrates that he saw Jesus as a savior, that his citations of the Hermetica are not in contradiction with basic Christian notions and that believed that the gods of Egypt were evil divine beings. His Christology and anthropology shares characteristics with “Classic Gnostic” theology and other early Christian notions. Also characteristic of the soteriologies presented in some heresiological reports, Zosimus described Jesus as teaching humans to “cut off” their body. This last observation, which is dependent on recognizing Zosimus as a Christian, shed light on the symbolism of the First Lesson on Excellence.